Tension Between Digital Legality Principle and Humanistic Punishment in Indonesian Criminal Code - Mulyono, Galih Puji; Nawawi Arief, Barda; Rozah, Umi (Jurnal Cakrawala Hukum, 2025)
The Indonesian National Criminal Code (Law No. 1 of 2023) introduces two fundamental changes to Indonesian criminal law: the expansion of the legality principle from a purely formal dimension to a material one by recognizing living law within society (Article 2), and the formulation of humanistic sentencing purposes that place human dignity as the ethical boundary of punishment (Articles 51–52). This article examines the tension between these two pillars in the context of digital crimes including personal data misuse, doxing, deepfake exploitation, and online gender-based violence which inherently evolve faster than legislative responses. Employing a normative legal research method with statutory, conceptual, and limited comparative approaches, this study finds that the expansion of the material legality principle does not automatically address cross-border and highly technical digital crimes, while the strict prohibition of analogy risks rendering criminal law unable to keep pace with emerging cyber-criminal modalities. To resolve this tension, this article proposes the concept of "humanistic digital legality principle," which rests on three dimensions: the protection of human dignity as a guiding principle for teleological-protective interpretation, technology-neutral norm drafting that meets the standard of foreseeability, and the integration of the National Criminal Code’s value framework with special legislation on digital crimes.